Advances in artificial life, evolutionary computation and systems chemistry : 10th Italian Workshop, WIVACE 2015, Bari, Italy, September 22-25, 2015, Revised selected papers /: 10th Italian Workshop, WIVACE 2015, Bari, Italy, September 22-25, 2015, Revised selected papers. (2016) - Unknown
No abstract available